Mechanical, thermal, electrical and flammability properties of rubber toughened polystyrene/graphene nanocomposites - Mat Desa, Mohd Shaiful Zaidi (2019)
Industrial needs and technological advancement drives the demand for lighter materials, resistant and is durable, has flexibility with viable cost. Thus arose polymeric composites with different types of use and application to know; aeronautics, aerospace, automobile and sporting goods. Development of polymer nanocomposite is an interesting area in advanced material research because of its capability of providing improved mechanical, thermal and electrical properties. In comparison to other materials the potential use of graphene based nanocomposites has attracted wide attention both for fundamental aspects as well as applications. The first part of this research is to investigate and demonstrate the effect of graphene contents on the mechanical, morphology and thermal properties of polystyrene-graphene (PS/G) nanocomposites. The PS/G nanocomposites was prepared with various of graphene nanoplatelets (G) contents (i.e. 0, 0.5, 1.0 and 1.5 wt%). The second part of this research is to determine the effect of styrene butadiene rubber (SBR) contents on the toughness of graphene reinforced polystyrene on the mechanical and morphological analysis. The PS/G/SBR nanocomposites was prepared with various of SBR contents (i.e. 0, 5, 10, 15 and 20 wt%) while the G contents were fixed at 0.5 wt%. The nanocomposites were prepared by melt blending technique in twin screw extruder. Later, the mechanical properties of nanocomposites (tensile, flexural and impact test), thermal properties (thermal gravimetric analysis (TGA) and the morphology were analyzed (scanning electron microscopy (SEM), transmission electron microscopy (TEM) and X-ray diffraction (XRD)). The thermal stability of polystyrene reinforced graphene improves when the temperature where decomposition starts to occurs are higher than decomposition temperature of pure polystyrene. Then, thermal conductivity of polystyrene shows the great improvement after the addition of graphene filler. The SBR domains present in PS prominently enhanced the elongation at break. Graphene reinforced polystyrene using SBR was effective in slightly enhancing the mechanical properties of polymer nanocomposites.